Adequacy evaluation of the annual colonoscopic surveillance and individual difference of disease phenotypes in Lynch syndrome. (6th May 2020) - Taniguchi, Fumitaka; Tanakaya, Kohji; Sugano, Kokichi; Akagi, Kiwamu; Ishida, Hideyuki; Nagahisa, Seiichi; Nishimura, Seitaro; Une, Yuta; Kimura, Yuji; Watanabe, Megumi; Utsumi, Masashi; Aoki, Hideki
Abstract: Background: Regular endoscopic surveillance for Lynch syndrome is reported to reduce colorectal cancer (CRC)-related mortality. However, the appropriate surveillance intervals are still unclear. We evaluated the adequacy of annual colonoscopy and investigated the differences in tumor occurrence rates between individual patients. Methods: In total, 25 patients with Lynch syndrome who underwent colonoscopic surveillance between 2007 and 2016 at the Iwakuni Clinical Center were included. We retrospectively investigated the surveillance frequency and the clinical features associated with tumor development. Results: Colonoscopic surveillance was performed every 397 days on average. A total of 101 tumors, including 8 intramucosal carcinomas and 15 carcinomas, were observed within the study period. Annual colonoscopy detected six malignancies, including a carcinoma requiring surgery. Tumor incidence was associated with tumor existence in the initial colonoscopies ( P  = 0.018). Patients with a tumor occurrence rate of 0.4 tumors per year during our observation period were significantly more likely to have malignancies detected during regular surveillance than patients who had a lower occurrence rate ( P  < 0.001). Malignancy occurrence rate was strongly associated with tumor occurrence rate ( P  < 0.001, R 2  = 0.44). Conclusions: Annual colonoscopic surveillance for Lynch syndrome patients was effective in reducing the risk of CRC progression, but was insufficient to completely avoid surgery. Because the tumor occurrence rate differed substantially between individuals, more intensive surveillance was required for high-risk patients. Abstract : Annual colonoscopic surveillance for Lynch syndrome patients was effective in reducing the risk of CRC progression. However, more intensive surveillance was required for high-risk patients depending on the tumor occurrence rate.